Genotype–phenotype correlation at codon 1740 of SETD2. Issue 9 (24th July 2020) - Rabin, Rachel; Radmanesh, Alireza; Glass, Ian A.; Dobyns, William B.; Aldinger, Kimberly A.; Shieh, Joseph T.; Romoser, Shelby; Bombei, Hannah; Dowsett, Leah; Trapane, Pamela; Bernat, John A.; Baker, Janice; et al.
Abstract: The SET domain containing 2, histone lysine methyltransferase encoded by SETD2 is a dual‐function methyltransferase for histones and microtubules and plays an important role for transcriptional regulation, genomic stability, and cytoskeletal functions. Specifically, SETD2 is associated with trimethylation of histone H3 at lysine 36 (H3K36me3) and methylation of α‐tubulin at lysine 40. Heterozygous loss of function and missense variants have previously been described with Luscan‐Lumish syndrome (LLS), which is characterized by overgrowth, neurodevelopmental features, and absence of overt congenital anomalies. We have identified 15 individuals with de novo variants in codon 1740 of SETD2 whose features differ from those with LLS. Group 1 consists of 12 individuals with heterozygous variant c.5218C>T p.(Arg1740Trp) and Group 2 consists of 3 individuals with heterozygous variant c.5219G>A p.(Arg1740Gln). The phenotype of Group 1 includes microcephaly, profound intellectual disability, congenital anomalies affecting several organ systems, and similar facial features. Individuals in Group 2 had moderate to severe intellectual disability, low normal head circumference, and absence of additional major congenital anomalies. While LLS is likely due to loss of function of SETD2, the clinical features seen in individuals with variants affecting codon 1740 are more severe suggesting an alternative mechanism, such as gain of function, effects on epigenetic regulation, or posttranslational modification of the cytoskeleton. Our report is a prime example of different mutations in the same gene causing diverging phenotypes and the features observed in Group 1 suggest a new clinically recognizable syndrome uniquely associated with the heterozygous variant c.5218C>T p.(Arg1740Trp) in SETD2.